Introduction to Excel 2007 - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This class teaches the basic functions and features of Excel 2007. After an introduction to spreadsheet terminology and Excel's window components, students will learn how to use the Help system and navigate worksheets and workbooks. Then they will enter and edit text, values, formulas, and pictures, and they will save workbooks in various formats. Students will also move and copy data, learn about absolute and relative references, and work with ranges, rows, and columns. This course also covers simple functions, basic formatting techniques, and printing. Finally, students will create and modify charts, and learn how to manage large workbooks."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 8, 2013).
Presenter, Pamela Conway.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets; Electronic books